Validação de método multirresíduo para determinação de pesticidas em alimentos empregando QuEChERs e UPLC-MS/MS. - QUEIROZ, S. C. do N. de (2012)
This paper presents a practical and rapid method which was validated for simultaneous quantification and confirmation of 29 pesticides in fruits and vegetables using ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). The samples were extracted following the method known as QuEChERS. Using the developed chromatographic conditions, the pesticides can be separated in less than 9 min. Two multiple reaction monitoring (MRM) assays were used for each pesticide. Four representative matrices (lettuce, tomato, apple and grapes) were selected to investigate the effect in recoveries and precision. Typical recoveries ranged from 70-120%, with relative standard deviation (RSDs) lower than 20%.